Exploring the Issues and Challenges of Deepfakes: A Doctrinal Study - Janees Rafiq (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2026)
Substantial advances in technology in the past few decades have allowed the production of content for specific categories of individuals. Some of these changes offer worries revolving around misinformation, particularly, differentiating between accurate and misleading information. The deliberate creation of untrue information from media outlets that are sent to a consumer’s feed along with real-time information is a particular kind of false information activity that might negatively impact a large portion of social media platforms. Fake photographs exist on the internet nowadays, and they appear to be harmless. We have undoubtedly witnessed the ‘Face Swapping’ features on Snapchat, or other such applications, where the users are allowed to change a person’s face with someone else. Most of the audience have also been a part of the ‘age yourself’ trend and see what they would look like during their old age. Apart from the fact that such applications are invented solely for entertainment, they are largely innocent since an individual can easily detect the difference between whether it is real or fake. This is the only reason why deepfakes are hazardous because they result in such images, which makes it impossible for normal human beings to recognize the difference between real and fiction. People have been manually and digitally manipulating and modifying videos and pictures for Deepfakes, irrespective of whether we recognize them or not, have already become a significant component of our everyday lives, as their usage on social networking sites, politics, the arts, and various other fields grows frequently. Aside from the troubling sexual abuse characteristics of deepfake technology, deepfakes were also used for enjoyment, training, and exploration in Hollywood, online forums, and the realm of politics. Deepfakes are an innovative and successful method for spreading lies. Their influence is calculated not only based on how convincing they are but also regarding their timeliness and authenticity of the disapproval of a deepfake.